El razonamiento lógico en el aprendizaje de la Matemática de los niños del Nivel Elemental de EGB. De la U.E. Alóag. - Toapanta Toapanta, Silvia Verónica (2020)
The present research was done within the process of teaching and learning mathematics, where the object of this researching is determined as a field of action to logical reasoning in the learning of mathematics linked to Basic sub-elementary Education, for which it was proposed as a general objective: elaborate an alternative for the development of logical cognitive in the learning of mathematics of children in the sub-elementary level of basic general education of the "Aloag" Education Unit. The research study was focused on a combination at a quantitative and qualitative level, thus leading to a bibliographical inquiry for the theoretical references, exploratory in the diagnosis of the current situation and field in the execution of the proposal for the solution of the problem. This managed to the design of a guide of didactic strategies of logical reasoning for the learning of mathematics by students of the elementary sublevel of general basic education (second, third and fourth); which was socialized with teachers working in the Education level and applied with students of second, third and fourth of Basic General Education parallel “A” of the morning day of the projected educational institution. The proposal was validated by expert criteria and user with teachers with experience in the educational field. With its application there was an improvement in students by solving arithmetic operations, abstract and logical thinking with geometric figures, problem solving and deductive and inductive mental agility with mathematical exercises and processes